Oral microbiome contributions to metabolic syndrome pathogenesis - Yue, Zijun; Fan, Yue; Shan, Guangliang; Chen, Xingming (Frontiers in Microbiology, 2025)
Comprising over 700 bacterial species, the oral microbiome is the second most diverse microbial community in the human body after the gut microbiome. Currently, existing review literature suggests that gut microbiome events may play a significant role in the pathogenesis of metabolic syndrome, but the role of the oral microbiome in this disease has not yet been reviewed. The oral-gut microbiome axis refers to a bidirectional regulatory system that facilitates interaction between the oral cavity and the gut through microbial pathways. The microbiota from these two sites can migrate between each other via pathways such as swallowing and blood circulation, which may participate in disease development. In addition to the oral-gut axis, the oral microbiome itself may also influence disease pathogenesis. This review examines the potential contributions of the oral microbiome in the pathogenesis of metabolic syndrome, emphasizing its impact on insulin resistance, systemic inflammation and adipokine secretion. We explore therapeutic strategies targeting the oral microbiome which hold promise as future treatments for metabolic syndrome. Future research is needed to further elucidate the causal relationship between the oral microbiome and metabolic syndrome and to develop personalized microbiome-based therapies.